Diversity and vegetative structure in an anthropized landscape of La Venta, Juchitán, Oaxaca, Mexico - Muñóz-Jiménez, Oscar; López Acosta, Juan Carlos; Villegas Patraca, Rafael (Instituto de Ecología, A.C., 2019)
Background and Aims: Human activities have changed the structure and composition of ecosystems. These activities can fragment the natural landscape. This heterogeneity could generate greater diversity that allows the maintenance of the basic functions of the ecosystem. An analysis of plant diversity in the area of La Venta, Oaxaca, is presented to infer how species can contribute to the conservation of biodiversity and maintaining the ecosystem functionality.Methods: Seven elements of the landscape were identified by satellite images: medium subperennifolious tropical forest (MSTF), deciduous forest (DF), DF secondary vegetation (DFSV), gallery forest (GF), vegetation strips (VS) and agricultural area (AGRO). Within these sites, indices of diversity α and β, similarity and indices of relative importance were calculated.Key results: A total of 303 taxons were recorded in the six elements of the anthropized landscape. Of these, 231 were identified up to species level, and 38 at genus level. The MSB was the element with the greatest richness with 131 species, while AGRO was the poorest with only 10 registered species. The patterns of composition, structure, richness and diversity reported in this study are consistent with what has been described for dry tropical forests.Conclusions: Each of the landscape elements described is probably playing an important role in biodiversity retention. On the one hand, elements such as the SMS and the SBC may be functioning as sources of food and shelter for species of flora and fauna most associated with conserved habitats, while the BG and the VF, on the other hand, may be contributing to the connectivity of the landscape, as they function as biological corridors.